Monitoring system based on fog computing - Machado, Miguel Chagas Bilhau (2017)
This thesis is a contribution of an architectural solution, describing a system that represents an extra layer of computing power, placed between the cloud and sensor networks, acting both as a mediator whose central task is to manage, monitor and collect data from geographically-located groups of sensor nodes and as a communication hub to the cloud with which data is exchanged in a compact and minimalist fashion. The latter is accomplished by designing nodes as autonomous entities, able to organise themselves in smaller groups, within the system. Additionally, these entities possess inherent mechanisms which aim to accomplish fault tolerance within groups of nodes, maintaining the status quo of the overall system while performing in an ubiquitous environment, continuously embracing contextual changes. The overall solution was tested in a proof of concept where we conceived three test cases that helped us validate it.